An effective method for high frequency multiple shoots regeneration and callus induction of Convolvulus Pluricaulisc choisy: an important medicinal plant - URVASHI CHANDEL; DR.SHIVALI KHAROLIWAL (International Journal of Pharma and Bio Sciences, 2017)
Convolvulus pluricaulis Choisy of family convolvulaceae is an indigenous plant mainly advocated as brain tonic. The protocol was developed which produce for shoot regeneration and callus induction. Studies on micro propagation of callus was undertaken in which explants were inoculated on MS medium fortified with various concentration of 2, 4-D(2,4-Dichlorophenoxy acetic acid) and BAP(6-Benzylaminopurine) and Kn(Kinetin).The best callus induction was observed on 2, 4-D (1.0mg/l and 2.0mg/l) also with various concentrations of BAP and Kn. Best regeneration of shoot was achieved when they were cultured on ms medium supplemented with BAP( 1- 3.0mg/l) and Kn(1.0 mg/l).The study of micro propagation has given a rapid improvement over conventional technique for multiplication and germplasm preservation of Convolvulus pluricaulis.Such medicinal plants can be used for the extraction of medicinally important compounds or for pharmacological studies.